Rate of Complications and Subsequent Shoulder Complaints for Non-operatively Managed Pediatric Proximal Humerus Fractures - Baker, Courtney; Larson, Noelle; Shaughnessy, William; Stans, Anthony; Milbrandt, Todd (Frontiers in Surgery, 2020)
Purpose: The purpose of the study was to describe the early complications and delayed shoulder complaints of non-displaced or minimally displaced pediatric proximal humerus fractures treated non-operatively. Methods: Retrospective review of all pediatric proximal humerus fractures at a single institution from 2001 to 2016. Inclusion criteria were: AP and axillary radiographs upon presentation and final follow up, one follow up appointment, either a non-displaced or minimally displaced fracture, and open physis. Exclusion criteria were: pathologic fractures, re-fractures, bone metabolic disorders. Patient demographics, injury characteristics, radiographic measurements and clinical exam findings were reviewed. Delayed shoulder complaints were defined as a visit to any provider for an ipsilateral shoulder or arm complaint after final scheduled fracture appointment. Results: Sixty-nine of 177 total pediatric proximal humerus fractures met inclusion criteria. Mean age was 10 years (SD = 3.4). Sixty-five had angulation <20 degrees. Median time to last scheduled follow up was 1.4 months (Interquartile range 0.8–1.4). At last scheduled follow up, 9 (13.0%) fractures had an altered exam. One (1.4%) fracture had a complication of a fall and re-fracture. Extraphyseal fractures were more likely to increase in angulation at short term follow up, but had no association with short or long term complications. No patient initially treated with non-operative management subsequently underwent operative treatment. There were three presentations (4.3%) to health professionals for subsequent shoulder complaints; one was treated with short courses of physical therapy and the other two were simply observed. Conclusions: Non-displaced or minimally displaced proximal humerus fractures treated non-operatively sustain rare short or long term complications with no cross over to operative management. Once non-operative management is pursued, these fractures may be amenable to surveillance with primary care or allied orthopedic staff after initial evaluation by pediatric orthopedic providers. Level of Evidence: Level III retrospective cohort study.